Impact of Professional Skepticism on Financial Statement Fraud Detection: An Empirical Study of External Auditors in Yemen (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study investigates the impact of professional skepticism on detecting financial statement fraud from the perspective of external auditors in Yemen. A quantitative analytical approach was employed, using a questionnaire as the primary data collection tool. The study population comprised 575 external auditors, from which a purposive sample of 392 auditors from both private and public sectors was selected. A total of 223 valid questionnaires were returned, yielding a 57% response rate. Statistical analysis using SPSS revealed a significant positive impact of professional skepticism on fraud detection, indicating that higher levels of skepticism enhance auditors’ ability to identify and evaluate fraudulent practices. This underscores professional skepticism as a critical factor in improving the effectiveness of external auditing. Accordingly, the study recommends systematically integrating professional skepticism into auditing standards and procedures to strengthen audit quality and enhance fraud detection effectiveness.
Keywords: Professional Skepticism; Detecting fraud in financial statements; External Auditors; Yemen